LEVERAGING DIGITAL TECHNOLOGY TO ENHANCE COGNITIVE AND FUNCTIONAL SKILLS OF LEARNERS WITH INTELLECTUAL DISABILITY - Udeme Samuel Jacob (Jurnal Tatsqif, 2025)
This research explores the application of digital technology in enhancing the cognitive and functional skills of learners with intellectual disabilities. As educational environments evolve, the integration of innovative technologies presents a unique opportunity to address the diverse needs of this population. Digital tools, such as interactive software, mobile applications, and virtual reality environments, offer tailored learning experiences that accommodate various learning styles and abilities. Using a systematic literature review study, the research highlights that these technologies can facilitate skill development in areas such as communication, problem-solving, and daily living activities. For instance, speech-generating applications can aid individuals in improving their verbal communication, while gamified learning platforms can engage learners in a dynamic and motivating manner. In addition, digital resources enable educators and caregivers to track progress and customise lesson plans, ensuring that each learner receives the support they require. Furthermore, the accessibility of technology is continually improving, making it easier for learners with intellectual disabilities to access these valuable tools.